Ecocide Is Genocide: Decolonizing the Definition of Genocide - Lauren J. Eichler (Genocide Studies and Prevention, 2020)
I demonstrate how the destruction of the land, water, and nonhuman beings of the Americas constitutes genocide according to Indigenous metaphysics and through analysis of the decimation of the American buffalo. In Genocide Studies, the destruction of nonhuman beings and nature is typically treated as a separate, but related type of phenomenon—ecocide, the destruction of nonhuman nature. In this article I follow in the footsteps of Native American and First Nations scholars to argue that ecocide and the genocide of Indigenous peoples are inextricably linked and are even constitutive of the same act. I argue that if justice is to be achieved for Indigenous peoples through the UN’s ability to prosecute genocide then the definition of genocide needs to, at minimum, include ecocide as a recognized act.